2016
DOI: 10.1111/php.12604
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiO2/CNT Composites and its Photocatalytic Activity Toward Sudan (I) Degradation

Abstract: Semiconductor photocatalysis has the potential for achieving sustainable energy generation and degrading organic contaminants. In TiO2 , the addition of carbonaceous nanomaterials has attracted extensive attention as a means to increase its photocatalytic activity. In this study, composites of TiO2 and carbon nanotubes (CNT) in various proportions were synthesized by the hydrothermal method. The crystalline structures, morphologies, and light absorption properties of the TiO2 /CNT photocatalysts were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The removal efficiency was further enhanced to 3.5 mg/g as CNTs were introduced to UiO-66, showing that CNTs could greatly enhance the photodegradation. It has been reported that the combination of CNTs and photocatalysts (e.g., TiO 2 ) can facilitate the charge transfer and reduce the recombination of photogenerated electron/hole pairs (Jiang et al, 2013b;Miribangul et al, 2016;Woan et al, 2009;Xie et al, 2010). Such a mechanism might contribute to the enhancement of UiO-66-CNT for the photodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…The removal efficiency was further enhanced to 3.5 mg/g as CNTs were introduced to UiO-66, showing that CNTs could greatly enhance the photodegradation. It has been reported that the combination of CNTs and photocatalysts (e.g., TiO 2 ) can facilitate the charge transfer and reduce the recombination of photogenerated electron/hole pairs (Jiang et al, 2013b;Miribangul et al, 2016;Woan et al, 2009;Xie et al, 2010). Such a mechanism might contribute to the enhancement of UiO-66-CNT for the photodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, a variety of semiconductor-CNT composite photocatalysts have been developed. For example, Miribangul et al [83] prepared a TiO 2 /CNT composite via a simple hydrothermal method. The influence of the CNT concentration in the TiO 2 -CNT composites on their photocatalytic activity was investigated and the 0.3 wt % CNT content in TiO 2 /CNT composite could offer the highest photocatalytic degradation of Sudan (I) in UV-vis light.…”
Section: Semiconductor/carbon Heterojunctionsmentioning
confidence: 99%
“…and noble elements (Pt, Pd or Rh) heteroatoms into metallic or carbonaceous catalysts has been demonstrated as an effective and practical route in various application such as lithium batteries, gas sensors, photocatalysis and electrochromic devices and adsorption. [20][21][22][23][24][25][26][27][28][29][30] However, for any practical application, at first, the cost and stability of the material must be considered. The anion and noble metal dopants do not have much practicability because of their inadequate stability, intricate preparation process, and costly initial material.…”
Section: Introductionmentioning
confidence: 99%